Understanding the mechanism of organic corrosion inhibitors through density functional theory - Shaker, L.M.; Al-Amiery, A .A.; Al-Hamid, M. A. I.; Al-Azzawi, W. K. (Korose a ochrana materiálu, 2024)
Organic corrosion inhibitors have been widely used to prevent and mitigate the damaging effects of corrosion on metal surfaces. However, their underlying mechanisms of action and effectiveness are still not fully understood. In recent years, the use of density functional theory (DFT) has emerged as a powerful tool to investigate the interaction between organic inhibitors and metal surfaces at the molecular level. This review article provides an overview of the principles of DFT, its advantages and limitations, and its application to the study of organic corrosion inhibitors. The factors affecting the performance of organic inhibitors, such as molecular structure, functional groups, and metal surface properties, are discussed in detail. The interaction between organic inhibitors and metal surfaces, including the adsorption and desorption of inhibitors, the role of intermolecular forces, and the effects of pH and temperature, are also explored. Finally, the challenges and future directions in the development of organic inhibitors using DFT are highlighted, including limitations and challenges in using DFT and potential avenues for further research. Overall, this review demonstrates the potential of DFT to provide valuable insights into the mechanism of organic corrosion inhibitors and to guide the development of new and more effective inhibitors for the protection of metal surfaces.